1999
DOI: 10.1111/j.1749-6632.1999.tb09446.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Parameters for the Bioelectrical Characterization of Breast Tissue

Abstract: In the data set collected by the authors in freshly excised breast tissue, the admittance loci generally differed from circular arcs, rendering the calculation of the usual set of parameters impossible. Alternative parameters were used for the analysis of these data. The present study consists of the definition and evaluation of a set of such parameters aimed at the characterization and differentiation of breast tissues. These parameters were defined so that their calculation does not require the fit of circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 14 publications
6
101
1
1
Order By: Relevance
“…Furthermore, the estimations of dielectric properties in scenario (iii) also agreed well with previous ex vivo studies such as [37,38,40,42]. However, Haemmerich et al [43] observed a change in some dielectric parameters after excising tissue and attributed those changes to variations of temperature, tissue dehydration and ischemic effects.…”
Section: Dielectric Propertiessupporting
confidence: 79%
“…Furthermore, the estimations of dielectric properties in scenario (iii) also agreed well with previous ex vivo studies such as [37,38,40,42]. However, Haemmerich et al [43] observed a change in some dielectric parameters after excising tissue and attributed those changes to variations of temperature, tissue dehydration and ischemic effects.…”
Section: Dielectric Propertiessupporting
confidence: 79%
“…Moderate result for sensitivity and specificity may be due to declining breast density among this age group of women (Milanese et al, 2006). As images for EIT depend on the capabilities of the software to map algorithmic calculations of electrical conductivity through breast tissues, low density breast may cause low quality of images (Jossinet and Schmitt, 1999). This study tends to be different from few studies which showed that the sensitivity and specificity of EIT and mammography were almost equal (Prasad et al, 2008;Raneta et al, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…Microwave scanning technique for breast cancer diagnosis depends on large discrepancies in dielectric properties between normal and tumor tissues [15][16][17][18][19]. The dielectric properties of breast tissue in diversified frequency ranges have been studied by many different research groups, demonstrating that differences in the relative permittivity are sufficient for the microwave image.…”
Section: Dielectric Properties Of Breast Tissuesmentioning
confidence: 99%
“…Microwave imaging depends on the dielectric properties of malignant tumor and surrounding tissues for breast cancer detection [15][16][17][18][19][20][21][22]. The dielectric properties of the tissues consist of two basic parameters called relative permittivity and conductivity.…”
Section: Dielectric Properties Of Breast Tissuesmentioning
confidence: 99%